Aislamiento, actividad biológica y caracterización bioquímica de lectina de semillas de chenopodium quinoa willd. (cv. Salcedo-INIA) - Huarachi-Valencia, Juan-Pablo (Instituto Universitario de Innovación Ciencia y Tecnología Inudi Perú, 2022)
Lectins act as cell recognition molecules, and probably in plant defense. The CqLEC, lectin from Ch. quinoa cv Salcedo INIA, was isolated, purified and characterized from 70 g of seeds through saline extraction, and the combination of two molecular exclusion chromatographies such as Sephadex G-100 and G -75, obtaining 5.53 mg/ml of protein with hemagglutinating activity, as well as by reverse phase HPLC at 32 minutes with 54% buffer B, indicating that it had a low number of hydrophobic residues in its structure. Likewise, SDS-PAGE showed that the purified lectin was homogeneous since it had a single component corresponding to a 12.82 kDa protein. Being that the CqLEC agglutinated human erythrocytes of the "O Rh+" blood group with an MHC of 1.95 μg/ml, inhibited by fucose (0.78 mM) and the chelating agent EGTA (0.1 mM), this indicated that would be a fucose-binding lectin dependent on divalent ions such as calcium or manganese. On the other hand, this protein showed specific bactoagglutination for E. coli (CMB equal to 200 μg/ml), as well as insecticidal activity against Symmetrischema plaesiosema larvae (1000 ppm of CqLEC, P < 0.05). Complete amino acid analysis revealed that CqLEC is an acidic lectin (70.54% hydrophilic residues and 29.46% hydrophobic residues), with glutamic acid (33%) prevailing, with a molecular mass of 12.859 kDa. By sequential homology study, it was determined that it belongs to the family of vegetable lectins of Legumes, showing 82.1% similarity with the precursor of agglutinin I extracted from the bark of Cladrastis kentukea. The CqLEC also presented highly conserved residues in its structure, such as Leu 4, Ser 6 and Phe 7.